Movimento interestadual das quebradeiras de coco babaçu: mulheres, trabalho e informação - Silva, Leididaina Araújo e (2014)
This dissertation presents the history of Interstate Movement of Babassu breakers (MIQCB), founded and led by women dedicated to this rural extractive activity. The movement has existed for 23 years and is organized in four Brazilian states (two of the Northeast - Maranhão and Piauí and two from North - Para and Tocantins). The study highlights the work of five women, coordinators/MIQCB the leaders in what refers to issues ranging from entry to the movement to informational issues related to movement. This is a qualitative study involving semi-structured interviews divided into five thematic sections focusing on the following aspects: demographic data and personal experience; characterization of regional activities and their role in these activities, informational issues and internal and external communication of the members, as well as the importance of the use of information and communication technologies (ICT) to the movement. The history of MIQCB is retold from the point of view of these five leaders interviewed, highlighting the conflicts and difficulties, as well as the victories and prospects for the movement in the future. Data analyses suggest that the legalization of the movement, the approval of the Free Babassu Law in the state of Tocantins and the integration of products derived from babassu palm tree in the commercial market, significantly marked the history of the movement. Some other aspects highlighted by the study are that these women feel strengthened as members of the movement and that their work is recognized and valued within the social and political context in which they live; that the dialogue between the movement, civil society and the government could be improved through new projects; that communication is strong within the movement although there are communication difficulties with state governments; that ICT use is extremely important for communication, strengthening of the group, and that there is concern to preserve the information and documentation of the relation to traditional knowledge of babassu breakers.